Flexible Networks of Patterned Conducting Polymer Nanowires for Fully Polymeric Bioelectronics. Issue 3 (4th December 2021) - Chapman, Christopher A. R.; Cuttaz, Estelle A.; Tahirbegi, Bogachan; Novikov, Alexey; Petkos, Konstantinos; Koutsoftidis, Simos; Drakakis, Emmanuel M.; Goding, Josef A.; Green, Rylie A.
Abstract : Patterning of conducting polymers (CPs) into fully functioning devices remains a challenge for the creation of polymeric bioelectronics. Presently, the most successful method for patterning CPs is preprocess blending with structural components and using either subtractive or additive processes to produce the desired design. This work focuses on the development and characterization of a filter‐based processing method for direct pattern transfer of the CP poly(3, 4‐ethylenedioxythiophene) (PEDOT) to elastomeric substrates. Laser sintering of a pattern into the surface of a filter membrane and the subsequent filtering of PEDOT nanowires onto the surface of the filter enable feature sizes of approximately 400 μm to be resolved without the need for any postprocessing. The resulting films of patterned PEDOT nanowires are found to possess high conductivity as well as improved wet electrochemical properties in comparison to platinum. Using the process developed in this work, thin and flexible arrays of PEDOT nanowire films are produced and used as an EMG device to test muscle contractions. Abstract : The development and characterization of a filter‐based processing method for direct pattern transfer of conducting polymer nanowires onto elastomeric substrates is accomplished through laser sintering of a filter membrane. Feature sizes of approximately 400 μm are achieved, and the resulting films of patterned nanowires are found to possess high conductivity with improved electrochemical properties in comparison to platinum.